2014
DOI: 10.1002/stem.1757
|View full text |Cite
|
Sign up to set email alerts
|

Neural Stem Cells Differentiated From iPS Cells Spontaneously Regain Pluripotency

Abstract: Differentiated somatic cells can be reprogrammed into pluripotent stem cells by transduction of exogenous reprogramming factors. After induced pluripotent stem (iPS) cells are established, exogenous genes are silenced. In the pluripotent state, retroviral genes integrated in the host genome are kept inactive through epigenetic transcriptional regulation. In this study, we tried to determine whether exogenous genes remain silenced or are reactivated upon loss of pluripotency or on differentiation using an in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 45 publications
(70 reference statements)
1
49
0
Order By: Relevance
“…Approximately two decades ago, we first determined the activity of the genomic fragment containing Oct4 using a β-galactosidase reporter and found that DE activity was ESC- and germ cell-specific and that PE was epiblast- and embryonic carcinoma cell (P19)-specific (Yeom et al., 1996). Oct4 -GFP transgenic mice have been generated and used for the detection of PGCs and PSCs and for monitoring reprogramming through nuclear transfer, cell fusion, and the transduction of reprogramming factors (Boiani et al., 2002, Choi et al., 2014, Do and Schöler, 2004). However, these existing transgenic systems cannot concurrently discriminate between the activity of DE and PE.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately two decades ago, we first determined the activity of the genomic fragment containing Oct4 using a β-galactosidase reporter and found that DE activity was ESC- and germ cell-specific and that PE was epiblast- and embryonic carcinoma cell (P19)-specific (Yeom et al., 1996). Oct4 -GFP transgenic mice have been generated and used for the detection of PGCs and PSCs and for monitoring reprogramming through nuclear transfer, cell fusion, and the transduction of reprogramming factors (Boiani et al., 2002, Choi et al., 2014, Do and Schöler, 2004). However, these existing transgenic systems cannot concurrently discriminate between the activity of DE and PE.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, iPSC generation using retroviral transduction was developed; however, it presented some challenges, the most important of which was the integration of exogenous transgenes into the host genome after viral transduction [8]. Ultimately, iPSC research aims to develop regenerative and therapeutic applications to cure intractable human diseases; therefore, this issue must be resolved before clinical trials.…”
Section: History Of Exogene-free Induced Pluripotent Stem Cellsmentioning
confidence: 99%
“…Injury, though, may restrict production of new neurons and oligodendrocytes by endogenous cells into the spinal cord. Some cell transplantation studies have demonstrated reduced differentiation of exogenous stem cells compared to the endogenous differentiation after grafting to a spinal cord [5]. Thus, the environment of the spinal cord has a restrictive or inhibitory action related to the differentiation of OPCs.…”
Section: Mesenchymal Stem Cells In Scimentioning
confidence: 99%